(untitled) - Landau, L. D. (Oxford, 1965)
This book is destined to play a major part in the future education of theoretical physicists.' Proceedings of the Physical Society This edition has been completely revised to include some 20% of new material. Important recent developments such as the theory of Regge poles are now included. Many problems with solutions have been added to those already contained in the book.
Keywords: Quantum theory,Lý thuyết lượng tử